Comparisons of Leg Joint Angles-Shooting Shoes vs Jogging Shoes (International Journal of Innovative Research in Computer Science & Technology, 2022)
The main factor in maintaining good  performance for air pistol athletes is to keep a stable  posture without physical change. In addition, the athletes  are ought to implement various approaches to enhance  their shooting performance. The athletes have attempted to  use different shoes to keep their balance intact. The present  study evaluated effects of different shoes on kinematics  (leg joint angles) of 8 elite shooters while performing air  gun shooting. The results suggested that there were no  statistical differences in either leg angles. The results  suggested that the shoes in the present study did not  influence kinematic changes of a body while performing  air gun shooting.
Keywords: Air gun; Shoes; Joint Angles; Stability